Seroprevalence of anti-SARS-CoV-2 antibodies in household domestic ferrets (Mustela putorius furo) in Spain, 2019–2023 - Jacobo Giner; María Eugenia Lebrero; Michele Trotta; Pablo Rueda; Laura Vilalta; Maite Verde; Ramón Hurtado-Guerrero; Julián Pardo; Delia Lacasta; Llipsy Santiago; Maykel Arias; Natacha Peña-Fresneda; et al. (Veterinary Research Communications, 2024)
SARS-CoV-2 is the causal agent of Coronavirus Disease 2019 (COVID-19) in humans that emerged in late 2019. This virus is able to infect humans and different animal species. Among pets, cats and ferrets are more susceptible to be infected by the SARS-CoV-2. Epidemiological studies are an important tool to provide information under natural conditions of exposure to SARS-CoV-2 virus. In comparison to cats, limited epidemiological studies have been performed in domestic ferrets ( Mustela putorius furo) reporting the presence of antibodies in this species. This study analysed the presence of anti-SARS-CoV-2 antibodies in 432 cliend-owned ferrets from different geographical areas of Spain during the different waves of COVID-19 outbreaks from December 2019 to May 2023 (42 months). For this purpose, anti-SARS-CoV-2 antibodies were detected by an enzyme-linked immunosorbent method (ELISA) using the receptor binding domain (RBD) of Spike antigen and confirmed by serum virus neutralization assay. Eighteen of the 432 ferrets included were seroreactive by the in-house ELISA (4.17%, 95% Confidence Interval (CI): 2.65–6.49). In this sense, the wave of COVID-19 with the higher number of seropositive ferrets occurred during the seventh wave when the different Omicron subvariants were the dominant virus variants. Our results suggest that the risk of SARS-CoV-2 transmission in domestic ferrets in natural conditions is low. Further research is need to evaluate the potential risk of transmission of SARS-CoV-2 from human to pets.